Group Classification of Nonlinear Schrödinger Equations - Nikitin, A. G.; Popovich, R. O. (Ukrains’kyi Matematychnyi Zhurnal, 2001)
We propose an approach to problems of group classification. By using this approach, we perform a complete group classification of nonlinear Schrödinger equations of the form iψ t + Δψ + F(ψ, ψ*) = 0.